A Rare Cause of Persistent Pulmonary Hypertension Resistant to Therapy in The Newborn: Short-Rib Polydactyly Syndrome - Nihat Demir; Erdal Peker; İbrahim Ece; Sultan Kaba; Kemal Ağengin; Oğuz Tuncer (Case Reports in Pulmonology)
Short-rib polydactyly syndrome is an autosomal recessively inherited lethal skeletal dysplasia. The syndrome is characterized by marked narrow fetal thorax, short extremities, micromelia, cleft palate/lip, polydactyly, cardiac and renal abnormalities, and genital malformations. In cases with pulmonary hypoplasia, persistent pulmonary hypertension of the newborn can develop. In this paper, we present a term newborn with persistent pulmonary hypertension of the newborn, which has developed secondary to short-rib polydactyly syndrome and was resistant to therapy with inhaled nitric oxide and oral sildenafil.